(untitled) (Journal of Nepalese Business Studies, 2016)
86 Product quality has entered the consciousness of organizations with a vengeance. It has become crystal clear that high-quality products have a distinct advantage in the market place, that market share can be gained or lost over the quality issue.Therefore, quality is a competitive priority. Quality is the only factor that ensures an organization’s survival and growth. Quality focuses on meeting consumer need, meeting the competition, improving continuously and extending these concerns to all phases of business. Today, it has been well understood by managers that the real price of poor quality is lost consumers and ultimately, the death of an organization. Therefore to be successful in today’s business environment ,organizations must pay attention to quality. Hence, a systematic procedure has to be evolved and followed and different concepts of quality management have to be understood clearly for designing and executing the quality management programme effectively. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp. 87-90